الميراث والوصية بين الفقه الإسلامي والقانون السريلانكي : دراسة تحليلية /‏ - Mohamad Arafath Careem Mohamad Jiffry (al-Jami'ah al-Islamiyah al-'Alamiyah, 2015)
The main focus of this study is to examine the law of Inheritance and Wills as applied to the Muslim community in Sri Lanka where the community constitutes the second largest minority of the total population of the country, through a systemized research conducted in the area of Fiqh and on the relevant existing law of the nation. Thus, the research involves mainly with the inconsistencies or differences between two distinct legal regimes, i.e. Shari'ah and the statutory law of the state in the field specified above. The research has revealed that matters related to Inheritance of Muslims will be dealt in accordance with the Shari'ah law while common law is applied when testacy matters are involved. It has been established by the supreme court of Sri Lanka that a child adopted by Muslim parents would not be entitled to become their heir as the matter is governed by the Act legislated in compliant with the principles of the Shari'ah. The research further scrutinizes the governing principles when the parties involved with the rights of inheritance are from different religions. The study also has analytically assessed the discordance between the Shari'ah and Wills Ordinance and it has found that a Muslim is not restricted from conveying his entire property unto his heir or heirs by way of a will as the law applicable in this regard is not Shari'ah but the statutotry law that is not compliant to Shari'ah principles.